Manajemen Pendidikan Islam Berbasis Fitrah Perspektif Humanistic Psychology - Finda Findiana; Hidayati (Universitas Muhammadiyah Jakarta, 2026)
This study is motivated by the tendency of Islamic education management to remain administrative and technocratic, thereby insufficiently accommodating the holistic development of human potential. This research aims to construct a model of Islamic education management based on the concept of fitrah within the perspective of humanistic psychology as a more integrative and human-centered approach. The study employs a qualitative method with a library research design, using scholarly documents such as books, peer-reviewed journal articles, and academic works as its primary data sources collected from both digital and printed repositories. The main instrument is the researcher, supported by a document analysis guide. Data were collected through documentation techniques and analyzed using content analysis and an interpretive approach. The findings reveal that integrating fitrah and humanistic psychology reconstructs education management into a human-centered system that emphasizes self-actualization, meaningful learning, and balanced development of intellectual, emotional, and spiritual dimensions. In conclusion, this approach offers a conceptual contribution to developing a holistic, humanistic, and contextually relevant model of Islamic education management.